2013
DOI: 10.1183/09031936.00001913
|View full text |Cite
|
Sign up to set email alerts
|

Clarithromycin increases linezolid exposure in multidrug-resistant tuberculosis patients

Abstract: The use of linezolid for the treatment of multidrug-resistant tuberculosis is limited by doseand time-dependent toxicity. Recently, we reported a case of pharmacokinetic drug-drug interaction between linezolid and clarithromycin that resulted in increased linezolid exposure. The aim of this prospective pharmacokinetic study is to quantify the effect of clarithromycin on the exposure of linezolid.Subjects were included in an open-label, single-centre, single-arm, fixed-order pharmacokinetic interaction study. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 30 publications
1
43
0
1
Order By: Relevance
“…Furthermore, a decrease in mortality in murine infection models [39,60] and synergistic effects when CLR was combined in vitro with second-line anti-TB drugs [36,37,40,57,73] were seen. Also, an interaction was reported in a clinical study [61], suggesting an increase of LZD serum concentration when combined with CLR.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Furthermore, a decrease in mortality in murine infection models [39,60] and synergistic effects when CLR was combined in vitro with second-line anti-TB drugs [36,37,40,57,73] were seen. Also, an interaction was reported in a clinical study [61], suggesting an increase of LZD serum concentration when combined with CLR.…”
Section: Discussionmentioning
confidence: 97%
“…One study described the influence of CLR on LZD exposure in five MDR-TB patients. While 250 mg CLR once daily had no statistically significant effect, 500 mg of CLR significantly increased LZD serum exposure by a median of 44% compared with baseline [61]. Another retrospective study reported that when CLR was included in a salvage regimen, this did not necessarily result in improved culture conversion [62].…”
Section: Clinical Studiesmentioning
confidence: 94%
See 2 more Smart Citations
“…Diacon, et al 48 (Continue) that a linezolid dose between 300 and 600 mg per day is adequate to treat MDR-/XDR-TB when added to OBR [52][53][54][55][56][57][58][59][60][61] .…”
Section: Re-proposed Drugsmentioning
confidence: 99%